Roles of Exosome Genomic DNA in Colorectal Cancer - Li, Xiaoshuai; Wang, Qiushi; Wang, Rui (Frontiers in Pharmacology, 2022)
Exosomes are extracellular vesicles that mediate cell-to-cell communication. Bioactive substances such as DNA, RNA, lipids, and proteins are present in it, and they play an essential role in pathogenesis of colorectal cancer (CRC). The role of RNA and protein in exosomes has been extensively studied. Exosome DNA has recently attracted the attention of a great deal of scientists. According to studies, exosome DNA mainly contains genomic DNA (gDNA) and mitochondrial DNA (mtDNA), of which exosome gDNA is widely used in liquid biopsy of CRCs. It includes a variety of clinically relevant tumor-specific mutation genes. In addition to liquid biopsy, researchers find that exosome gDNA regulates immune and metabolic functions in CRCs, making it an important research object. However, the primary research on exosome gDNA is still limited. Here, we describe the occurrence and composition of exosomes. Summarizes the essential characteristics and mode of action of exosome gDNA. Remarkably, this paper constitutes a comprehensive summary on the role of exosome gDNA on CRC with the intent of providing a theoretical basis and reference for early diagnosis and clinical treatment of cancer.